Adsorption behaviours and mechanisms of heavy metal ions' impact on municipal waste composts with different degree of maturity. Issue 22 (2nd October 2019) - Liu, Ling; Guo, Xiaoping; Zhang, Chengliang; Luo, Chao; Xiao, Chaoqun; Li, Ruoyu
ABSTRACT: Composting may change the adsorption characteristics and mechanisms of organic materials due to their differences in organic chemical functional groups and surface structures. The adsorption properties of heavy metals onto the municipal solid waste compost (MSW-C) and its secondary fermentation form (MSW-SC) were comparatively investigated in single, binary and multiple solutions by batch experiments. In the single-metal system, the maximum adsorption capacities of Cu, Zn, Cd and Ni onto MSW-SC were 29.2, 26.3, 38.1 and 22.0 mg g −1, respectively, and showed higher than that of MSW-C. The adsorption fitted best with the pseudo-second-order kinetics and Langmuir isotherms. The competitive adsorption results indicated that the composts exhibited good selectivity in the adsorption of Cu over Cd, Zn and Ni; thus, for the quaternary-metal systems, the adsorption sequence was Cu > Zn > Cd > Ni. Humic acid content, cation exchange capacity and surface area were increased following the secondary composting. FTIR analysis indicated amine and aromatic compounds were main binding sites accounting for metal sorption. SEM–EDX analysis suggested that the MSW-SC had rough surfaces and stronger adsorption capacity. Decreasing percentage of exchangeable metals was found in the metal-loaded MSW-SC based on a speciation analysis. This study highlights the interactive impacts of different metals during adsorption by compost with different maturity, the secondary composting process was a multifunctional improvement of sorption characteristics and MSW-SC was developed to be a highly efficient biosorbent. GRAPHICAL ABSTRACT: